The role and significance of the FIS Ski Jumping World Cup competitions held in Zakopane, Poland - Banbula, J. (Studies in Sport Humanities, 2013)
Ski jumping has become one of the most significant and popular winter sports in Poland. The successes of ski jumper Adam Malysz created a great interest among the Poles in this niche sport. The FIS Ski Jumping World Cup competition held annually in Zakopane has truly become the most important sport event of the season. The aim of the following paper is to discuss the significance of the Zakopane ski jumping competition for tour- ism development in the Podhale region of Poland. The author also evaluates the impact of the competition on the improvement of tourism attractiveness of Zakopane and Poland as well as on popularization of winter games, especially ski jumping, with a special emphasis on the importance of Adam Malysz`s successes. Theoretical considerations are supplemented by results of questionnaire survey conducted on a group of ski jumping spectators during the 2011 Zakopane competition. The research clearly shows that the mentioned sports event greatly affects the quality of promotion of Poland and Zakopane.